RANGE: Gene Transfer of Reversibly Controlled Polycistronic Genes - Yiwei Chen; Liji Cao; Chonglin Luo; Désirée AW Ditzel; Jörg Peter; Rolf Sprengel (Elsevier, 2013)
We developed a single vector recombinant adeno-associated viral (rAAV) expression system for spatial and reversible control of polycistronic gene expression. Our approach (i) integrates the advantages of the tetracycline (Tet)-controlled transcriptional silencer tTSKid and the self-cleaving 2A peptide bridge, (ii) combines essential regulatory components as an autoregulatory loop, (iii) simplifies the gene delivery scheme, and (iv) regulates multiple genes in a synchronized manner. Controlled by an upstream Tet-responsive element (TRE), both the ubiquitous chicken β-actin promoter (CAG) and the neuron-specific synapsin-1 promoter (Syn) could regulate expression of tTSKid together with two 2A-linked reporter genes. Transduction in vitro exhibited maximally 50-fold regulation by doxycycline (Dox). Determined by gene delivery method as well as promoter, highly specific tissues were transduced in vivo. Bioluminescence imaging (BLI) visualized reversible "ON/OFF" gene switches over repeated "Doxy-Cycling" in living mice. Thus, the reversible rAAV-mediated N-cistronic gene expression system, termed RANGE, may serve as a versatile tool to achieve reversible polycistronic gene regulation for the study of gene function as well as gene therapy.